2016
DOI: 10.1038/srep29019
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Ti60 Alloy under a Solid NaCl Deposit in Wet Oxygen Flow at 600 °C

Abstract: The corrosion behavior of Ti60 alloy covered with a solid NaCl deposit in wet oxygen flow at 600 °C has been studied further by SEM, EDX, XPS, XRD, TEM and EPMA analysis. The results show that solid NaCl and H2O react with Ti oxides, which destroyed the Ti oxide scale to yield the non-protective Na4Ti5O12 and other volatile species. The resulting corrosion product scale was multilayered and contained abundant rapid diffusion channels leading to the fast diffusion which improved the corrosion rate. A possible m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
(33 reference statements)
3
12
0
Order By: Relevance
“…Meanwhile, a corrosion scale is formed by the outward diffusion of Ti which results in a 15 μm loose layer that is observed under the corrosion products. Hence, the corrosion product scale is non-protective and the corrosion of pure Ti is greatly accelerated by solid NaCl in an O 2 + H 2 O environment at 600 ˚C, which is similar with the observation for several Ti alloy 11,[18][19][20] .…”
Section: Resultssupporting
confidence: 85%
“…Meanwhile, a corrosion scale is formed by the outward diffusion of Ti which results in a 15 μm loose layer that is observed under the corrosion products. Hence, the corrosion product scale is non-protective and the corrosion of pure Ti is greatly accelerated by solid NaCl in an O 2 + H 2 O environment at 600 ˚C, which is similar with the observation for several Ti alloy 11,[18][19][20] .…”
Section: Resultssupporting
confidence: 85%
“…None of them proposed a clear mechanism. They only showed parabolic-like [21,22] or parabolic-then-linear [19] oxidation kinetics, whose weight gains appeared, in the first case, 6-10 times larger than those observed in dry air. In each case, damaged corrosion scales (porous, cracked and non-adherent) were observed.…”
Section: Introductionmentioning
confidence: 89%
“…Very few studies reported a degradation of the oxidation resistance of Ti-6Al-2Sn-4Zr-2Mo-Si alloy or close-composition alloys under solid NaCl deposits [19][20][21][22][23]. None of them proposed a clear mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal barrier or ultra-refractory materials have been widely used as protective coatings for components exposed to high temperatures (from 550 to 900 °C) in aerospace and applications such as turbine blades and steam generators in power plants 1 4 . Generally, the most used materials used for thermal barrier coatings are metal superalloys 1 , 5 and yttria-stabilized-zirconia (YSZ) and YSZ-based systems 2 , 6 , 7 . Those materials have excellent chemical stability at high temperatures, good anti-corrosion properties and low thermal conductivity 7 , however, most of the superalloys and YSZ-based materials are brittle and lack of high hardness and wear resistance which restrict the applications where the materials are subject to high stresses and loads.…”
Section: Introductionmentioning
confidence: 99%